WORM and bipolar inkjet printed resistive switching devices based on silver nanocomposites. (24th April 2017) - Rajan, K; Bocchini, S; Chiappone, A; Roppolo, I; Perrone, D; Castellino, M; Bejtka, K; Lorusso, M; Ricciardi, C; Pirri, C F; Chiolerio, A
Abstract: In the present study, silver nanocomposite resistive switching devices were fabricated by inkjet printing, specifically designed inks onto planar symmetrical electrodes. The printed devices show different memory/switching behaviours according to the printed pattern and number of ejected drops (in turn according to the total ejected ink volume). A drop-on-position print results in a random access type memory with a rectifying ratio of 10 3 . The effect of compliance upon switching was studied. It was observed that an increase in the compliance current changed the switching behaviour of the device to bipolar and non-volatile with an On/Off ratio of 10 4 . A print-on-the-fly method resulted in a write-once-read-many device instead, where once a low resistance state was reached, the device was unable to recover its initial high resistance state. The present study gives an insight into the field-induced formation of conductive silver filaments, resulting in resistance switching. The active switching matrix ink formulation enabled easy deposition onto various substrates, thus widening printed electronics potential.